The mitochondrial NAD kinase functions as a major metabolic regulator upon increased energy demand - Hyunbae Kim; Zhiyao Fu; Zhao Yang; Zhenfeng Song; El Hussain Shamsa; Thangal Yumnamcha; Shengyi Sun; Wanqing Liu; Ahmed S. Ibrahim; Nathan R. Qi; Ren Zhang; Kezhong Zhang (Molecular Metabolism, 2022)
Objective: The mitochondrial nicotinamide adenine dinucleotide (NAD) kinase (MNADK) mediates de novo mitochondrial NADP biosynthesis by catalyzing the phosphorylation of NAD to yield NADP. In this study, we investigated the function and mechanistic basis by which MNADK regulates metabolic homeostasis. Methods: Generalized gene set analysis by aggregating human patient genomic databases, metabolic studies with genetically engineered animal models, mitochondrial bioenergetic analysis, as well as gain- and loss- of-function studies were performed to address the functions and mechanistic basis by which MNADK regulates energy metabolism and redox state associated with metabolic disease. Results: Human MNADK common gene variants or decreased expression of the gene are significantly associated with the occurrence of type-2 diabetes, non-alcoholic fatty liver disease (NAFLD), or hepatocellular carcinoma (HCC). Ablation of the MNADK gene in mice led to decreased fat oxidation, coincident with increased respiratory exchange ratio (RER) and decreased energy expenditure upon energy demand triggered by endurance exercise or fasting. On an atherogenic high-fat diet (HFD), MNADK-null mice exhibited hepatic insulin resistance and glucose intolerance, indicating a type-2 diabetes-like phenotype in the absence of MNADK. MNADK deficiency led to a decrease in mitochondrial NADP(H) but an increase in cellular reactive oxygen species (ROS) in mouse livers. Consistently, protein levels of the major metabolic regulators or enzymes were decreased, while their acetylation modifications were increased in the livers of MNADK-null mice. Feeding mice with a HFD caused S-nitrosylation (SNO) modification, a posttranslational modification that represses protein activities, on MNADK protein in the liver. Reconstitution of an SNO-resistant MNADK variant, MNADK-S193, into MNADK-null mice mitigated hepatic steatosis induced by HFD. Conclusion: MNADK, the only known mammalian mitochondrial NAD kinase, plays important roles in preserving energy homeostasis to mitigate the risk of metabolic disorders.